Search for polarisation in LOFAR data - Moszczynski, Niklas (My University, 2019)
The Low Frequency Array (LOFAR) is a new-generation digital radio telescope centred in the Netherlands and with international stations located in several European countries, including Sweden. The sensitivity, angular resolution, and survey speed of LOFAR makes it an ideal instrument to conduct high-quality observations of the entire northern sky in a poorly unexplored part of the electromagnetic spectrum at frequencies below 180 MHz. LOFAR is anticipated to detect millions of new radio sources. Most of them are extragalactic sources powered by accretion of matter onto supermassive black holes at the centres of galaxies. LOFAR can detect synchrotron radiation produced by relativistic electrons accelerated by magnetic fields. Measuring the polarisation of the radiation makes it possible to gain insight into the intrinsic properties of the sources and of the magnetised plasma along the line of sight (between the sources and the observer) via Faraday rotation. In this work, I have analysed data from the ongoing LOFAR survey and developed a new computer code in Matlab to search for polarisation in the large (and rapidly increasing) LOFAR dataset. In the future, it is likely that the use of neural networks will enable significant advances in this type of studies.
Keywords: LOFAR, Polarised sources, Synchrotron emission, Faraday rotation, Faraday dispersion function, Faraday cube, LoTSS, Neural networks